Developing individuals whilst managing teams: perspectives of under 21 coaches within English Premier League football - Dowling, C.; Reeves, M. J.; Littlewood, M. A.; Nesti, M.; Richardson, D. (Soccer & Society, 2018)
The aim of this study was to explore under 21 Development coaches` thoughts, perspectives, and approaches within this phase of development at English Premier League (EPL) football clubs. Data were collected via one-to-one semi-structured interviews with six under 21 development coaches from six different EPL clubs. Data were subjected to thematic analysis. Findings suggested that under 21 development coaches were situated, culturally and sometimes physically, in-between the academy and first team environments, trapped between two distinct cultures. Under 21 coaches also had contrasting views and approaches with regards to the development of under 21 players and the importance of winning at this stage of development. Participants appeared to favour creating environments that can replicate the first team environment to prepare under 21 players for the transition. The study concludes by proposing more support for under 21 development coaches is required from key stakeholders, regarding clarity of the role and players development.